Strategi Kontingensi Dalam Menghadapi Kondisi Pandemi Covid 19 ( Studi Kasus Qualitative Di PT Thara Perkasa Sejahtera, Jakarta, Indonesia ) - Septha Fifdityajaya Sutadisastra; Adhy Firdaus; Syafrudin Makmur (Jurnal Ilmiah Ekonomi Manajemen & Bisnis, 2024)
This study aims to understand the contingency strategies employed by companies in response to the negative impacts of the Covid-19 pandemic on the real estate development sector. This qualitative research adopts a case study approach, focusing on PT Thara Perkasa Sejahtera in Jakarta. Data was collected through interviews with company directors and employees, observations, and document analysis to capture the steps taken to mitigate the pandemic's impact. The data were analyzed by classifying the various data types and correlating them with information obtained from literature, documents, surveys, interviews, and field observations. The analysis reveals that the company's strategy to counter the negative economic effects of the Covid-19 pandemic includes: 1) Maintaining trust by communicating and fulfilling all obligations and rights of stakeholders, 2) Ensuring synergy by building productive internal collaborations and harmonious partnerships with stakeholders to produce beneficial and high-quality work, and 3) Promoting collaboration to generate ideas and solve complex problems towards a shared vision. Employees have experienced positive outcomes from these contingency strategies, including active communication between management and employees, which minimizes conflicts, fosters mutual trust, increases responsibility and a sense of ownership, and enhances employee participation and potential. Ultimately, these actions have led to increased motivation and productivity among the human resources at PT Thara Perkasa Sejahtera